PERAN HUMAS PEMERINTAH DI ERA KETERBUKAAN INIFORMASI (Analisis Isi Permenpan-RB No. 6 Tahun 2014 tentang Jabatan Fungsional Pranata Humas dan Angka Kreditnya) - Ika Karlina Idris (Jurnal Universitas Paramadina, 2014)
guaranteeing their right to information. In 2008, President SBY establishedLaw No. 14/2008 on Transparency of Public Information (UU KIP), which requires public agency to conduct a public information service and as a guarantee for citizen's right to access information. The one who plays an important role in implementing transparency of public information is government public relations (PR) agency, who is obliged to give  information to the citizen. It means that PR has an important role in  guaranteeing Indonesia's citizens a right of access to information,  promoting citizens' participation in public policy making, and implementing  the clean, transparent, and good governance. This paper  analyzes the roles of public relations in Indonesia's government regulation  (Peraturan Menteri Pendayagunaan Aparatur Negara dan  Reformasi Birokrasi Republik Indonesia No. 6/ 2014 on Public Reations  Functional and Its Credit Score). This paper analyzes whether the  government public relations has function as the public information officer  or still as the tools of government propaganda using PR's roles theory by  Broom and Dozier and government PR's goals by Baker. This research  finds that the regulation puts government PR officer as communication  technician (50%), expert prescriber (30,55%), communication facilitator  (16,66%), and problem solving facilitator (2,78%). This research finds that  the goals of government PR is to develop and protect positive  institutional images (42,2%), serve information to public (38,9%),  generate public feedback (11,92%), and persuade and win public acceptance (1,83%). The result of this research shows that even though government PR has a potential role in promoting public participation in Indonesia's new democracy, but it is still positioned as a propaganda  tools.